Can a Sunset Clause Derail an Amendment to the U.S. Constitution? - Kouroutakis, Antonios (De Gruyter, 2025)
Former President Biden, a couple of days before the end of his term in office, issued a statement acknowledging the passage of the Equal Rights Amendment (ERA) as the 28th amendment. The ERA was a proposed amendment to the United States Constitution approved by both chambers of Congress with bipartisan support in 1972 explicitly prohibiting sex discrimination. As stipulated by the amendment process outlined in the United States Constitution (Article V), for an amendment to be ratified, it must be approved by two-thirds of both houses of Congress. Then, it must be ratified by three-fourths of the state legislative bodies or threefourths of state constituent conventions. In essence, 38 states are required to ratify the proposed amendment. In 2020, the Virginia state legislature ratified the ERA, becoming the 38th state to meet the formal requirement of the amendment process. Despite the ratification from the State of Virginia, the status of the ERA as the 28th amendment to the US Constitution is disputed because of a sunset clause. This article offers fresh light on the validity of such amendment.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas; sunset clause; amendment; Equal Rights Amendment (ERA)